Improving Disaster Preparedness Services for People with Disabilities - Istiarsyah, Istiarsyah; Kamarullah, Kamarullah; Setiawan, Robiansyah; Dawi, Amir Hasan (Department of Special Education, 2023)
Lack of disaster preparedness has contributed to many disaster victims, especially people with disabilities, who are often neglected in making disaster risk reduction plans. In light of the recent World Conference on Disaster Risk Reduction (WCDRR) in Sendai, Japan, and the Sendai Framework for Disaster Risk Reduction (SFDRR) 2015-2030, which establishes new priorities for disaster risk reduction over the next 15 years, this issue has become a hot topic since then. This paper aims to contribute ideas to the Indonesian government in reforming and improving disaster preparedness services for people with disabilities based on successful theories, research, and practices developed in several countries. Through reviewing literature studies related to the issue and interviewing relevant informants in Indonesia, both data sources coped with six strategies that may contribute to improving disaster preparedness for disabled individuals. The strategies as the results of this study are intended to be used as reference material, particularly by the Indonesian National Disaster Management Agency (BNPB), in order to aid in the creation of a framework to better comprehend the communication, mobilization, transportation, and medical requirements of people with disabilities in the context of preparing disaster preparedness program scenarios.